Pengaruh Diferensiasi Produk, Harga dan Segmentasi Pasar Terhadap Volume Penjualan Unit Mobil All New Veloz Agung Toyota Batam Centre - Oktavia, Aii Melia Putri; Armansyah, Armansyah; Chartady, Rachmad; Alamsyahbana, Muhammad Isa (Universitas Batam, 2025)
To create a company's customers, implement a good marketing strategy that starts from within the company, one of the strategies that needs to be done is differentiation strategy. The product differentiation and varied prices presented by Toyota on the All New Veloz are expected to provide many choices that consumers can choose from to support their daily mobility with cars and support sales volume. The purpose of this study is to find out how the Influence of Market Differentiation and Segmentation on the Sales Volume of All New Veloz car units at the Agung Toyota Batam Centre. The type of research used is a quantitative descriptive research method, using primary and secondary data, as well as data collection techniques in the form of questionnaires which are carried out by distributing to the respondents as many as the number of samples that have been determined, namely 66 respondents from the number of buyers of the All New Veloz car unit at Agung Toyota Batam Center in the last 6 months which amounted to 66 buyers. The results of the study obtained are known that the regression equation obtained is Y= 10.646 + 0.443X1 + -0.551X2 + 0.737X3 + e which can be interpreted that the variables X1 and X2 have a positive and significant effect on the variable Y. and it is known that the results of the determination coefficient test show the value of Adjusted R Square which is 0.421 or 42.1%. Thus, 42.1% is the value of the contribution of the influence of product differentiation variables, prices, and market segmentation on sales volume. While the remaining 57.9% is the influence of other variables that were not studied in this study.